2019
DOI: 10.1177/1759720x19877131
|View full text |Cite
|
Sign up to set email alerts
|

Autologous costal chondral transplantation and costa-derived chondrocyte implantation: emerging surgical techniques

Abstract: It is a great challenge to cure symptomatic lesions and considerable defects of hyaline cartilage due to its complex structure and poor self-repair capacity. If left untreated, unmatured degeneration will cause significant complications. Surgical intervention to repair cartilage may prevent progressive joint degeneration. A series of surgical techniques, including biological augmentation, microfracture and bone marrow stimulation, autologous chondrocyte implantation (ACI), and allogenic and autogenic chondral/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 149 publications
(170 reference statements)
0
23
0
Order By: Relevance
“…31 The graft's growth seen more in the growing rabbits than the adults, indicating there might be a strong influence on the growth process of growing rabbits due to hormonal and growth factors. 10,29,32 In case of a few growing rabbits the graft grew mostly in width than in length and there were no sign of graft resorption. This observantion can be explained according to Timo Peltomaki et al 29 by local factors such as possible postoperative asymmetric jaw functions, and particularly uneven loading of the grafts due to changed food habbit, this might influence the structure of the graft and eventually on its growth.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…31 The graft's growth seen more in the growing rabbits than the adults, indicating there might be a strong influence on the growth process of growing rabbits due to hormonal and growth factors. 10,29,32 In case of a few growing rabbits the graft grew mostly in width than in length and there were no sign of graft resorption. This observantion can be explained according to Timo Peltomaki et al 29 by local factors such as possible postoperative asymmetric jaw functions, and particularly uneven loading of the grafts due to changed food habbit, this might influence the structure of the graft and eventually on its growth.…”
Section: Discussionmentioning
confidence: 96%
“…This bone remodeling or osteogenesis process might be because of osseous metaplasia 31 or previously calcified graft was used. Calcification of rib is a natural progression that should be carefully evaluated preoperatively using ultrasonography or dual-energy CT imaging 32 . Due to the lack of availability of these investigations this study depended on the visual difference in the color of the costochondral junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembled neocartilage implants made with costal chondrocytes have also been used to treat cartilage defects in Yucatan minipig models [ 19 ]. Transplantation and autologous chondrocyte implantation procedures in the clinic have also been performed [ 20 ]. For example, recent first-in-human efforts include using costal chondrocytes in a pellet-type autologous chondrocyte implantation to treat full-thickness lesions in knee articular cartilage [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It protects the cartilage against fibroblastic invasion, which is responsible for chondrocyte destruction [ 8 ]. Again the perichondrium is a dense connective tissue and is the precursor of chondrogenic cells [ 9 ], especially the proliferating chondrocytes, which play an essential role in mandibular growth [ 3 ]. Experimental studies on animals also showed that costochondral regeneration comes from the perichondrium [ 10 ].…”
Section: Introductionmentioning
confidence: 99%